Emblematic codes of Hryhorii Skovoroda’s dialogue A Colloquy, called “Alphabet,” or “Primer of Peace” - Soletskyi, Oleksandr (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
The paper focuses on the features, origin, and functions of Hryhorii Skovoroda’s (1722–1794) emblematic language (speech) in the dialogue A Colloquy, called “Alphabet,” or “Primer of Peace”. The objective is to study the emblematic arrangements of Hryhorii Skovoroda within the European emblematic literature context, focusing on eventual intertextual relations and striking semiotic interactions. The text of the paper interprets the artistic and stylistic features of the emblematic construction of eide of the Ukrainian writer, their sources, contexts, and the author’s conceptual nominations. Theoretical generalizations are made primarily from the text of Skovoroda’s dialogue A Colloquy, called “Alphabet,” or “Primer of Peace”, as well as from his other works, the scholars’ works, and the European literary context. The structural-semiotic methodology has been employed to trace the identified issues. The main idea of the paper is to highlight the dominance of the emblematic way of meaning stating in Hryhorii Skovoroda, thus, the emblematic code as the core in the sense-modelling activities. Emblematic forms have a special place in the coverage of anthropological, metaphysical, ethical, aesthetic, and hermeneutic eide of the Ukrainian poet and philosopher. Skovoroda considers emblematics as a particularly effective visual-verbal (iconic-conventional) type of signification functioning as a kind of refined meta-language, an ancient arcane semiosis practice of intellectuals. He had his personal insight into the nature, structure, and potential of such an expression, which was elaborated by the long-term, permanent hermeneutics of biblical texts, formed on the logic and metaphysics of ancient philosophers, the context of literary and artistic baroque, European emblematic models. Skovoroda uses significative re-referencing as a means of interpretation, therefore, individual images, embodied in the word, resemble semiotic bunches, concise visual-verbal meaning-making entities, disclosed through associations, comparisons, oppositions, metaphors, and structural-emblematic representation.